Early phase trials of novel hearing therapeutics: Avenues and opportunities - Schilder, Anne G.M.; Su, Matthew P.; Mandavia, Rishi; Anderson, Caroline R.; Landry, Evie; Ferdous, Tanjinah; Blackshaw, Helen (Hearing research, 2019)
Novel hearing therapeutics are rapidly progressing along the innovation pathway and into the clinical trial domain. Because these trials are new to the hearing community, they come with challenges in terms of trial design, regulation and delivery. In this paper, we address the key scientific and operational issues and outline the opportunities for interdisciplinary and international collaboration these trials offer. Vital to the future successful implementation of these therapeutics is to evaluate their potential for adoption into healthcare systems, including consideration of their health economic value. This requires early engagement with all stakeholder groups along the hearing innovation pathway. •Novel hearing loss therapies are rapidly progressing along the translational pathway.•To develop precision medicine for inner ear disorders, precision diagnosis is needed.•There is an urgent need for large-scale genotype–phenotype studies.•Clinical trials capability and capacity must increase in line with this growing field.•For implementation, it is vital to consider health economics and service impact.